2001
DOI: 10.1016/s0042-6989(00)00311-4
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic and achromatic defects in patients with progressing glaucoma

Abstract: To evaluate the pattern of losses associated with glaucomatous injury in patients with progressing glaucoma, functional losses were examined in 14 patients with progressing glaucoma using tests for which detection should be selectively mediated by one of three psychophysical mechanisms. Red-on-white increments, blue-on-white increments and critical flicker frequency were used to isolate the responses of the red-green chromatic mechanism, the blue-on chromatic mechanism, and the high-frequency flicker achromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…Pan et al confirmed the findings of Pearson et al 5 with chromatic stimuli and extended their approach by using Gabor patches. 6 However Pan et al were restricted to using only eight locations, to allow the use of 12-reversal staircases without fatiguing the subjects.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Pan et al confirmed the findings of Pearson et al 5 with chromatic stimuli and extended their approach by using Gabor patches. 6 However Pan et al were restricted to using only eight locations, to allow the use of 12-reversal staircases without fatiguing the subjects.…”
Section: Discussionsupporting
confidence: 61%
“…Another form of sinusoidal stimuli with low spatial frequencies (0.25 and 0.50 cyc/deg) is used in frequency-doubling perimetry (FDP), and the results of studies on test-retest variability with FDP are consistent with the predictions of Pearson et al 5 FDP defects are generally similar in depth to defects with conventional perimetry, when expressed as log contrast sensitivity, and test-retest variability is independent of sensitivity. 7,8 However, normal between-subject and test-retest variability are high for FDP.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…5,[10][11][12] However, there is now histologic evidence of damage in all 3 major visual pathways 3 -magnocellular, parvocellular, and koniocellular-as well as psychophysical evidence of early damage in red-green and blue-yellow channel processing, which are related to the parvocellular and koniocellular pathways. 13,14 These findings support the reduced redundancy hypothesis. 15 This postulates that the increased sensitivity of certain tests 13,16,17 is explained by the stimulation of specific and sparse subsets of ganglion cells, without the redundancy afforded by the other cell types.…”
supporting
confidence: 76%
“…It was surprising since the perimetry is the main functional test related to the diagnosis of very frequent and important ocular disease, the glaucoma [5][6][7][33][34][35][36] but also in other retina impairment as in the diabetes [37][38][39][40][41], multiple sclerosis [10,[42][43][44], mercury intoxication [20,45], and drug intoxications with hydroxichloroquine [16,[46][47][48][49], vigabatrin [18,50] and others. A possible explanation could be since glaucoma initially shows periphery reductions in visual field the authors were much more interested and focused in study those alterations than the central ones.…”
Section: Discussionmentioning
confidence: 99%